Equality of opportunity and health in post-COVID world - Alexi Gugushvili (Elsevier, 2021)
Links between equality of opportunity and health in post-COVID world must be an issue of general interest to academic, health, and policy audiences in the developed countries and other parts of the world. We already know that COVID-19 disproportionally affects most vulnerable and marginalised groups, while their positions in social hierarchy are strongly shaped by intergenerational transmission of advantages and disadvantages. Further, recent evidence from the United States and Europe also suggests that inequality of opportunity has significant negative consequences for health. This correspondence end with a call that decision makers, while rebuilding the post-COVID social model, should remember that equality of opportunity is not only fair but it is also good for health.